2022
DOI: 10.3389/fcimb.2022.1015633
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of ampc beta-lactamase producing escherichia coli and klebsiella pneumoniae isolates obtained from urine samples at a tertiary care hospital in the caribbean

Abstract: IntroductionThe aim of this study was to investigate the prevalence and distribution of AmpC beta-lactamases (BLs) in uropathogens (E. coli and K. pneumoniae) at the University Hospital of the West Indies Jamaica (UHWI).MethodDe-duplicated consecutive urine samples, collected from January to March 2020 at the UHWI, were analyzed. Screening and phenotypic confirmatory tests were conducted using resistance to cefoxitin and the Disc Approximation Test (DAT) respectively, for isolates of interest. Multiplex PCR wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…According to another study, all Escherichia coli isolates tested positive for the bla CIT family [29,30]. As noted in this study, DHA and CIT AmpC β-lactamases gene were commonly identified, indicating rapid plasmid expression and gene dissemination in recent times in the study area.…”
Section: Discussionsupporting
confidence: 58%
“…According to another study, all Escherichia coli isolates tested positive for the bla CIT family [29,30]. As noted in this study, DHA and CIT AmpC β-lactamases gene were commonly identified, indicating rapid plasmid expression and gene dissemination in recent times in the study area.…”
Section: Discussionsupporting
confidence: 58%